Determinação in silico de epítopos para uso no diagnóstico sorológico das febres de Chikungunya e Mayaro - Silva, David José Ferreira da (2019)
Chikungunya virus (CHIKV) and Mayaro virus (MAYV) are mosquito-borne viruses of medical importance. Both viruses can cause febrile illness ranging from mild symptoms to severe arthralgia. Clinical signs, especially in the acute phase, are confused with those of other arboviruses, such as dengue virus, yellow fever, and Zika virus. Therefore, laboratory diagnosis of CHIKV and MAYV is critical, especially in areas where arboviruses co-circulate. Herein, we describe an in silico approach to identify B-cell epitope suitable for the specific serodiagnosis of CHIKV and MAYV infections. We report two specific antigenic epitopes, one for CHIKV (ChikBP16) and other for MAYV (MayBP17), both located on the surface of the glycoprotein E2. These epitopes are suitable to be used as antigens in immuno-detection systems, although further in vitro validation is advised to ensure their effectiveness.